Perbandingan Reaksi Pasar Sebelum dan Sesudah Pengumuman Kasus Covid-19 Pertama (Event Study Pada Perusahaan Sektor Agrikultur yang Terdaftar di Bursa Efek Indonesia) - Indah Kusumawati; Indah Purnamawati; Resha Dwi Ayu Pangesti Mulyono (Akuntansi : Jurnal Akuntansi Integratif, 2022)
This study was conducted to examine and analyze the differences in market reactions before and after the announcement of the first COVID-19 case in Indonesia. This type of research is comparative quantitative using secondary data on stock prices, outstanding shares and trading volume of shares of agricultural sector companies listed on the Indonesia Stock Exchange in 2020. The research sample selection used purposive sampling technique, so that the number of samples from agriculture sector companies was 21 observational data. Hypothesis testing in this study used the paired samples t-test with the normality test using the Kolmogorov-Smirnov test. The results showed that the market reaction proxied by cumulative abnormal return and trading volume activity did not have a significant difference between before and after the announcement of the first Covid-19 case in Indonesia in agricultural sector companies. Based on these results, there is a tendency that market participants do not capture the information content of the announcement of the Covid-19 case that makes the market react.